Surrogacy Laws in Indonesia, Iran, and India: A Comparative Analysis of Legal Protections for Surrogate Mothers and Children - Dewa Gede Dedy Farendra; Kadek Julia Mahadewi (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
This study investigates Indonesia’s absence of a comprehensive surrogacy framework, a gap that leaves surrogate mothers and children in legal limbo and social precarity. By contrast, Iran authorizes surrogacy through Shia jurisprudence and enforceable contracts, while India governs the practice via the Surrogacy (Regulation) Act 2021, allowing only altruistic arrangements and banning commercial transactions. Using normative legal research and a comparative approach, the analysis synthesizes statutory provisions, religious edicts, and judicial precedents and evaluates enforcement mechanisms alongside socio-ethical implications across the three systems within diverse cultural, religious, and regulatory environments and illustrates divergent policy rationales. Findings show that Indonesia’s outright prohibition, unaccompanied by detailed implementing rules, denies parties any legal protection, whereas Iran and India offer more structured, coherent safeguards. The study therefore urges Indonesia to draft a rights-based, culturally responsive regulatory framework that harmonizes domestic values with international human rights standards. Such legislation is essential to secure legal certainty, uphold ethical principles, encourage transparent medical practice, and protect the most vulnerable actors, especially surrogate mothers and the children born through surrogacy arrangements.